2013
DOI: 10.1007/s12035-013-8518-3
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Reduces Neuronal Damage and Promotes Locomotor Recovery via Inhibition of Apoptosis After Spinal Cord Injury in Rats

Abstract: Autophagy is an intracellular catabolic mechanism that maintains the balance of proteins, lipids and aging organelles. 3-Methyladenine (3-MA) is a selective inhibitor of autophagy, whereas rapamycin, an antifungal agent, is a specific inducer of autophagy, inhibiting the protein mammalian target of rapamycin. In the present study, we examined the role of autophagy, inhibited by 3-MA and enhanced by rapamycin, in a model of acute spinal cord injury in rats. We found that rapamycin could significantly increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
125
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(134 citation statements)
references
References 42 publications
7
125
1
1
Order By: Relevance
“…24 Over the past few years, calcitriol has been reported to upregulate the level of autophagy-that is, it can induce autophagy in the SH-SY5Y neuroblastoma cell line as a model of Parkinson's disease. 7 In addition, calcitriol shows biochemical protective effects in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine mouse model of Parkinson's disease through induction of autophagy. 25 The present study showed the levels of LC3-II and Beclin1 proteins, representing increased autophagy flux, but the level of p62 protein, which was degraded through the autophagy-lysosomal pathway, decreased in the SCI rats treated with calcitriol compared with the SCI group.…”
Section: Effects Of Calcitriol On Sci K-l Zhou Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…24 Over the past few years, calcitriol has been reported to upregulate the level of autophagy-that is, it can induce autophagy in the SH-SY5Y neuroblastoma cell line as a model of Parkinson's disease. 7 In addition, calcitriol shows biochemical protective effects in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine mouse model of Parkinson's disease through induction of autophagy. 25 The present study showed the levels of LC3-II and Beclin1 proteins, representing increased autophagy flux, but the level of p62 protein, which was degraded through the autophagy-lysosomal pathway, decreased in the SCI rats treated with calcitriol compared with the SCI group.…”
Section: Effects Of Calcitriol On Sci K-l Zhou Et Almentioning
confidence: 99%
“…Furthermore, recent evidence suggests that stimulation of autophagy after SCI contributes to nerve cell selfprotection and locomotive recovery. 7 Calcitriol (C 44 H 80 O 4 Si 2 , also known as 1,25-dihydroxyvitamin D 3 ), which has biological functions in bone and calcium metabolism, has a key role in osteoporosis. However, calcitriol has recently been shown to have a number of bioactivities.…”
Section: Introductionmentioning
confidence: 99%
“…Kanno et al [18] found that rapamycin reduced locomotor impairment and neuronal death after spinal cord injury in mice. This effect of rapamycin was reported to be mediated through activation of autophagy by inhibiting the mammalian target of rapamycin (mTOR) signaling pathways [36].…”
Section: Introductionmentioning
confidence: 99%
“…30,31) Moreover, poor therapeutic value of 3-MA treatment has also been reported in traumatic spinal injury models. 32,33) In cerebral ischemia studies, substantial evidence suggests 3-MA inhibits autophagy activation and maturation, reduces I/R injury, and improves cell survival in vivo and in vitro. 34,35) An intrathecal injection of 3-MA was administered to enable the drug to enter the cerebrospinal fluid to directly act on the injured spinal nerves.…”
Section: Discussionmentioning
confidence: 99%